Identification of stable and adaptable hybrid Rice genotypes (SAARC Journal of Agriculture, 2015)
Development of varieties with high yield potential coupled with wide adaptability is an important plant breeding objective. Presence of genotype and environment (G×E) interaction plays a crucial role in determining the performance of genetic materials, tested in different locations in different years. This study was under taken to assess yield performance, stability and adaptability of seventeen hybrid rice genotypes evaluated over 12 environments. The analysis of variance for growth duration and grain yield (t ha-1) for genotype, environment year, environment × genotype, year × environment, year × genotype and year × environment × genotype were highly significant (p